Peace of Mind (1946): Judaism and the Therapeutic Polemics of Postwar America - Heinze, Andrew R. (Religion and American culture, 2002)
A full-page ad in the September 30, 1946, issue of Life magazine shows a picture of a book called Peace of Mind being handed down from above by a male hand. “This New Best Seller,” the caption reads, “will help you find the happiness you have always sought.” Life readers may have wondered if the hand was supposed to be the author's, the publisher's, or the Lord's, but, in any case, it would have been Jewish. The author was a rabbi, the publisher was Simon and Schuster, and the God in question was the God of Moses rather than Jesus. The mysterious hand might have belonged to yet another Jew, as the book was the first religious best-seller to endorse Freud. In the advertisement, Harvard psychologist Gordon Allport testified that author Joshua Loth Liebman “shatters the long-standing myth that religion and psychology are necessary antagonists [and] proves that they converge upon a single goal - the enhancement of man's peace of mind.”